(untitled) (Fiep Bulletin - online, 2014)
The Physiotherapy groceries currently encompasses several areas of expertise, which are part of his field of work, and the Acupuncture the newest to be incorporated in this framework for action, reflecting controversy between a group of medical professionals and acceptance among other professionals and patients. In order to clarify this controversy. The work took a critical review of literature, which addresses on the profile of the main aspects historical, ethical and clinical trials of Acupuncture in Brazil in the vision of Physiotherapy. The strategy consisted methodological steps literary criticism about acupuncture (Chinese medicine); Searches through literature in articles, books, magazines virtual, among others. Where observed that Acupuncture faced difficulties in their social, political and clinic in Brazil, even knowing that it is embedded in the area of health in SUS as practice integrative and complementary health as a whole.